2021
DOI: 10.1108/jpbm-01-2020-2718
|View full text |Cite
|
Sign up to set email alerts
|

The impact of service category and brand positioning on consumer animosity in the service sector – a social identity signaling perspective

Abstract: Purpose The present research responds to researchers’ calls for more research of consumer animosity on potential boundary conditions (e.g. product categories) and marketing strategies that may mitigate such negative impacts on marketers’ product and/or brand performance, with a special focus on the soft service sector. This paper aims to address the unique characteristics of service internationalization, i.e. cultural embeddedness, hybridized country origins and high consumption visibility, by proposing a soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 90 publications
(166 reference statements)
0
8
0
Order By: Relevance
“…Furthermore, as Escalas (2012), Yang et al . (2018) and Fong et al. (2021) confirmed that the self-identity of a consumer displays a consistent relationship with their purchasing choices.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Furthermore, as Escalas (2012), Yang et al . (2018) and Fong et al. (2021) confirmed that the self-identity of a consumer displays a consistent relationship with their purchasing choices.…”
Section: Introductionmentioning
confidence: 68%
“…Therefore, academia has been quick to provide insights on green purchasing, where consumers' environmental knowledge and concern, the consumer decision-making process, implications of consumer attitudes and the impact of product attributes as well as previous purchase experiences have an impact on purchasing decisions (Sharma and Foropon, 2018;Costa et al, 2021;Chowdhury and Samuel, 2013;Yadav and Pathak, 2016). Furthermore, as Escalas (2012), Yang et al (2018) and Fong et al (2021) confirmed that the self-identity of a consumer displays a consistent relationship with their purchasing choices. Hence, consumers' purchasing behavior would depend on their personal connection to products developed through self-identity and social pressure, where the consumer needs to maintain a social identity (Escalas, 2012;White et al, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…As a result, individuals often behave consistently with these group expectations to maintain their associations with the group and other members (Tajfel et al ., 1979). Marketing research demonstrates that consumers identify with brands that echo and strengthen their self-identities through their engagement with the brand communities (Fong et al ., 2021). Members of brand communities engage in collective behaviors, such as sharing norms, to extol the virtues of their beloved brands and help other brand identifiers (An et al ., 2019).…”
Section: Theoretical Foundation – Social Identity Theorymentioning
confidence: 99%
“…Specifically, we examine the moderating effect of usage in public vs. in private on the relation between anticipated severity of social sanctions arising from consumption and purchase intentions. Public and private usage situations refer to the extent to which a product is predominantly used in private or in public, and thus the degree to which the behavior is visible to others (Davvetas and Diamantopoulos, 2016;Fong et al, 2021;Josiassen and George Assaf, 2013). Public usage denotes conditions where behavioral visibility is at a higher degree, whereas private usage refers to conditions where consumption visibility is at a lower degree.…”
Section: Consumption Context: Utilitarian Influencementioning
confidence: 99%
“…That is, consumption visibility (i.e. social visibility of consumption) may exert an impact on consumption decisions (Davvetas and Diamantopoulos, 2016;Fong et al, 2021;Maher and Mady, 2010). In the case of low consumption visibility, the consumer is the only evaluator of the product; whereas, in the case of high consumption visibility, the public are also able to evaluate the product (Josiassen and George Assaf, 2013).…”
Section: Consumption Context: Utilitarian Influencementioning
confidence: 99%